CXCL4 deficiency limits M4 macrophage infiltration and attenuates hyperoxia-induced lung injury - Bingrui Yu; Siyuan Jia; Yu Chen; Rong Guan; Shuyu Chen; Wanwen Tang; Tianping Bao; Zhaofang Tian (Molecular Medicine)
Abstract Background Bronchopulmonary dysplasia (BPD), a chronic lung disease prevalent among premature infants, significantly impacts lifelong respiratory health. Macrophages, as key components of the innate immune system, play a role in lung tissue inflammation and injury, exhibiting diverse and dynamic functionalities. The M4 macrophage, a distinctive subtype primarily triggered by chemokine (C-X-C motif) ligand 4 (CXCL4), has been implicated in pulmonary inflammatory and fibrotic processes. Nonetheless, its contribution to the pathophysiology of BPD remains uncertain. Objective This study aimed to elucidate the involvement of CXCL4 in hyperoxia-induced neonatal lung injury and fibrosis, with a particular focus on its influence on M4 macrophages. Methods A BPD model in neonatal mice was established through continuous exposure to 95% O2 for 7 days. Comparative analyses of lung damage and subsequent regeneration were conducted between wild-type (WT) and CXCL4 knockout (KO) mice. Lung tissue inflammation and fibrosis were assessed using histological and immunofluorescence staining, enzyme-linked immunosorbent assay, Western blot, and real-time quantitative polymerase chain reaction. Differentiation of M0 and M4 macrophages was performed in vitro using macrophage colony-stimulating factor and CXCL4, while expressions of S100A8 and MMP7, along with migration assays, were evaluated. Results Elevated CXCL4 levels and M4 macrophage activation were identified in the lung tissue of BPD model mice. CXCL4 deficiency conferred protection to alveolar type 2 epithelial cells, reduced sphingosine-1-phosphate metabolic activity, mitigated pulmonary fibrosis, and limited M4 macrophage progression. This deletion further enhanced lung matrix remodeling during recovery. In vitro, CXCL4 promoted M4 macrophage differentiation and increased macrophage migration via chemokine (C-C motif) receptor 1. Conclusion CXCL4 contributes to hyperoxia-induced lung injury and fibrosis through modulation of cytokine release, alveolar cell proliferation, lipid metabolism, and the regulation of macrophage phenotype and function.